Numerical simulation of an inviscid transonic flow through a channel with a leap - Lisewski, P. (Archives of Mechanics, 1997)
A two-dimensional inviscid transonic channel flow of a perfect gas is considered. The gas of relatively high pressure, flows into a channel through a converging nozzle. The channel geometry is characterised by a discontinuity of cross-section at the nozzle outlet. A fast, explicit differential algorithm based on a two-step Lax-Wendroff scheme is used to solve the set of Euler equations. Results of calculations are compared with the visualised flow and with the measured pressure distributions. The computed steady-state flow field agrees well with measurements.